Constitutive modelling of hydrolytic degradation in hydrogels - Pan, Z; Brassart, LGC (Elsevier, 2022)
Biodegradable synthetic hydrogels have emerged as promising materials for tissue engineering and drug/cell delivery applications. However, their successful implementation requires precise understanding of the degradation response in terms of mechanical properties, swelling, and mass loss. In this work, we develop a thermodynamically-consistent continuum framework and constitutive models for coupled large deformation and hydrolytic degradation in hydrogels. In particular, we propose constitutive models for the evolution of elastic modulus and polymer mass loss based on a description of the evolving network topology during hydrolysis. The theory is validated against experimental data for two model hydrogel systems with different network architectures, namely biodegradable Tetra-PEG hydrogels and PLA-b-PEG-b-PLA hydrogels. We have also implemented our model in a finite element software. We show that our model is capable of simulating degradation-induced heterogeneous swelling in scenarios relevant to biomedical applications. Our theory and constitutive models could be useful for the design of hydrogels with controlled degradation behaviour.